1385. Concomitant Administration of Liquid Porcine Circovirus-free Human Rotavirus Vaccine with Routine Pediatric Vaccines Does Not Impact Immune Responses in Infants: Results from a Phase 3, Randomized Trial in the United States. (31st December 2020) - Abu-Elyazeed, Remon; Klein, Nicola P; Moerman, Leentje; Povey, Michael; Pruitt, Anthony; Senders, Shelly; Silas, Peter; Bi, Dan
Abstract: Background: Porcine circovirus type 1 (PCV-1) material was detected in the human rotavirus vaccine (HRV) in 2010. Although no safety risk was identified for infants vaccinated with HRV, a PCV-free HRV (no detection of PCV-1 and PCV-2 according to the limit of the tests used) was developed, which showed comparable immunogenicity and safety profile to the initial HRV. We assessed the non-inferiority of immune responses elicited by routine vaccines (co-)administered with either liquid (Liq) PCV-free HRV or lyophilized (Lyo) HRV, and the immunogenicity and safety of HRVs in infants. Methods: In this phase 3, randomized, single-blind study (NCT03207750) in the United States, healthy infants aged 6–12 weeks received 2 doses of Liq PCV-free HRV or Lyo HRV at study month (M)0, M2 and routine vaccines at M0, M2, M4 (Figure 1 ). Co-primary objectives were to hierarchically demonstrate non-inferiority of immune responses to routine vaccine antigens when (co-)administered with Liq PCV-free HRV compared to Lyo HRV, 1 month post-dose 3 of the routine vaccines and to rule out a 10% decrease in seroresponse to pertussis antigens. Immunogenicity and safety of HRVs were also evaluated (Figure 1 ). Figure 1. Study design Results: 1272 infants were vaccinated and 990 (Liq PCV-free HRV: 489; Lyo HRV: 501) were included in the per-protocol set. All statistical criteria were met for the 2 co-primary objectives (Table 1 ). Seroprotection/seropositivity rates were ≥ 99.3% for all DTaP-HBV-IPV antigens, ≥ 97.4% for Hib and ≥ 90.8% for most PCV13 serotypes. Geometric mean concentrations/titers for the routine vaccine antigens were comparable between groups (Table 2 ). 76.3% of infants in Liq PCV-free HRV and 78.9% in Lyo HRV had anti-RV antibody concentration ≥ 20 U/mL. The incidence of solicited (Figure 2 ) and unsolicited adverse events (AEs) were similar in both groups. Of 75 serious AEs (SAEs), 2 (Lyo HRV: abdominal distension; intussusception) were considered vaccine-related by investigator; 1 fatal SAE (Liq PCV-free HRV: sudden infant death syndrome) was considered non-vaccine related by investigator. Table 1. Non-inferiority of the immune responses to routine vaccine antigens when (co-)administered with HRV (Liq PCV-free HRV vs Lyo HRV) and exclusion of 10% decrease in seroresponse to pertussis antigens, 1 month post-dose 3 (per-protocol set) Table 2. Seroprotection/seropositivity rates and geometric mean concentrations/titers for the routine vaccines antigens 1 month post-dose 3 (per-protocol set) Figure 2. The incidence of solicited adverse events occurring within 7 days post-vaccination (overall/infant, exposed set) Conclusion: Routine vaccines (co-)administered with Liq PCV-free HRV showed non-inferior immune responses and similar safety profiles compared to (co-)administration with Lyo HRV. Funding: GlaxoSmithKline Biologicals SA Disclosures: Remon Abu-Elyazeed, MD, PhD, GSK group of companies (Employee) Nicola P. Klein, MD, PhD, GSK group of companies (Research Grant or Support)Merck (Grant/Research Support)Pfizer (Grant/Research Support)Protein Science (now SP) (Grant/Research Support)Sanofi Pasteur (Grant/Research Support) Leentje Moerman, PhD, GSK group of companies (Employee) Michael Povey, MSc, GSK group of companies (Employee) Shelly Senders, MD, Pfizer (Grant/Research Support) Dan Bi, MD, MPH, GSK group of companies (Employee)